PENGARUH PENERAPAN AUDIT INTERNAL, WHISTLEBLOWING SYSTEM, DAN SURPRISE AUDIT TERHADAP PENCEGAHAN FRAUD PADA LEMBAGA PERKREDITAN DESA DI KECAMATAN BLAHBATUH - Made Agus Adi Suputra (UNHI Press, 2021)
Lembaga Perkreditan Desa (LPD) is a financial institution owned by the Desa Pakraman in Bali. In maintaining and developing strategy and productivity, the LPD's operational activities will be guided and supervised. However, in recent years, there have been many cases of fraud in the LPDs caused by weak supervision from both internal and external parties. A positive work environment can be realized by implementing a whistleblowing program for employees to report violations of the code of conduct and maximizing the role of internal audit by conducting regular surprise audits. With a whistleblowing system, conducting regular internal audits and surprise audits within an institution, it is very important to monitor internal performance. This study uses data from Lembaga Perkreditan Desa in the Blahbatuh District. Determination of the sample in this study using simple random sampling method, with the number of observations of 120 research samples. The data analysis technique is multiple linear regression analysis, because it uses more than one independent variable. Based on the analysis, it is known that the whistleblowing system, internal audit, and surprise audit variables have a positive and significant effect on fraud prevention at Lembaga Perkreditan Desa in Blahbatuh District.